Penentuan Musim Tanam dan Waktu Tanam Padi Sawah Berdasarkan Akumulasi Curah Hujan Sepuluh Hari Hitung Maju dan Mundur di Kelurahan Lempake Kota Samarinda - Bambang Supriyanto (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2012)
A method is presented to determine the onset and termination of the wet season, based on forward and backward accumulation of 10 day (decade) rainfall totals. Morris and Zandstra (1979) choose 75 mm accumulated of rainfall as the onset time for the growing season for dry seeded crops, and 200 mm accumulated rainfall for initiation of pudling (wet land preperation of rice fild)The propose of the research is determination of planting season and time of planting low land rice (Oriza sativa Linn) at Lempake village. The research conducted from July until Setember 2012Result of this research showed that planting season of lowland rice begins at decade III January until decade l November and the first planting time begins Januari and second in May.